2008
DOI: 10.1111/j.1572-0241.2008.02035.x
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Protein-Induced Proctocolitis in Childhood

Abstract: Cow's milk protein-induced proctocolitis presents with overt rectal bleeding in otherwise healthy infants and is characterized by an eosinophilic infiltrate of the left colonic mucosa. Although it is the most common cause of proctocolitis in infancy, dietary protein-induced proctocolitis had hardly ever been reported in childhood so far. We hereby report 16 otherwise healthy children aged 2-14 yr, who presented over a 6-yr period with persistent or recurrent rectal bleeding related to a mild form of left-sided… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(38 citation statements)
references
References 21 publications
3
33
1
Order By: Relevance
“…Similar histological data were reported in school-age children with rectal bleeding due to allergic procto-colitis ( 48 ). It is also interesting that in 70 of 206 (35 % ) patients with NCWS and CM protein hypersensitivity, we found the presence of lymphoid hyperplasia in the colon mucosa ( 7 ).…”
Section: Non-celiac Wheat Sensitivity and Food Allergysupporting
confidence: 73%
“…Similar histological data were reported in school-age children with rectal bleeding due to allergic procto-colitis ( 48 ). It is also interesting that in 70 of 206 (35 % ) patients with NCWS and CM protein hypersensitivity, we found the presence of lymphoid hyperplasia in the colon mucosa ( 7 ).…”
Section: Non-celiac Wheat Sensitivity and Food Allergysupporting
confidence: 73%
“…Ravelli et al reported 16 cases of rectal bleeding that resolved with elimination of cow's milk protein in children aged 2 to 14 years. Endoscopic and histologic findings were additionally consistent with FPIAP [34]. It is not clear, however, whether this is the same clinical entity.…”
Section: Clinical Manifestations and Presentationmentioning
confidence: 74%
“…FPIAP has long been known to be a common cause of rectal bleeding in small infants. Recently, however, a series of 16 children between 2 and 14 years of age was described, with features remarkably similar to those observed in infancy FPIAP, providing evidence that FPIAP also affects older children [7]. In the current study, 7 patients (group 2) with these features were included.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a microarray analysis of mucosal biopsy specimens demonstrated that the expression of CCL11 and CXCL13, but not TH1-, TH2-, or TH17-related molecules, was significantly enhanced in these patients [6]. Although the condition is largely considered a disease of small infants, a recent report described FPIAP also in older children (age 2-14 years), with features remarkably similar to those observed in infancy [7]. Of note, an adult form of eosinophilic colitis, which is not related to food allergy and tends to have a less favorable prognosis, has also been described in rare individuals [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation